Development of the Internet of Things (IoT) in early detection of emergencies using postpartum alert - Cicilia, Fitri; Runjati, Runjati; Latifah, Leny (MEDISAINS, 2024)
Background:  IoT-based postpartum alert is the development of a vital sign-checking tool using obstetric early warning system indicators. This is an effort to prevent maternal death during the postpartum period. Monitoring is carried out manually without interpretation and recommendations and is not connected to the Internet. Adding interpretations and recommendations and connecting to the Internet can help mothers and families with self-examination and remote monitoring by midwives or health workers because, generally, mothers are at home during the postpartum period.Purpose: This research aims to create and test an IoT-based Postpartum alert detection tool that has been developed. Methods: This research is R&D, divided into five stages: collecting information through literature study, product/model design, design validation, design revision, and small-scale product/model testing.Results:  An IoT-based early postpartum detection tool with a portable design has been created. The test results are based on the Receiver Operating Characteristic (ROC) classification in the area under the ROC curve, which shows that the tool has an outstanding category with an accuracy level of 90%.Conclusion: The IoT-based postpartum emergency detection alarm is a vital sign measuring tool that can interpret and recommend signs and connect to health workers using internet features. The measurement and interpretation results are sent to the cloud system to provide recommendations, data storage, and notification alarms to health workers.